Synthesis of a novel slow-release potassium fertilizer from modified Pidgeon magnesium slag by potassium carbonate. (2nd August 2016) - Li, Yongling; Cheng, Fangqin
ABSTRACT: A novel slow-release potassium fertilizer (SPF) was synthesized using Pidgeon magnesium slag (PMS) and potassium carbonate, which could minimize fertilizer nutrient loss and PMS disposal problems. Orthogonal experiments were conducted to determine the optimum conditions for synthesis. The potassium (K)-bearing compounds of SPF existed mainly in the form of crystalline phases Ca1.197 K0.166 SiO4, K2 MgSiO4, and K4 CaSi3 O9, and in the noncrystalline phase. The active silicon content of SPF was 2.09 times as much as that of magnesium slag, and the slow-release character of SPF met the requirement for partly slow-release fertilizer in the national standard (GB/T23348-2009). The best models for describing the K release kinetics in water and 2% citric acid were the Elovich model and the first-order model, respectively. The heavy metal contents of SPF conformed to the national standard for organic–inorganic compound fertilizers, and the leaching mass concentrations of heavy metals and Fluorine were far lower than the limit values of the identification standard for hazardous waste identification for extraction toxicity (GB5085.3-2007), and also met the class II quality standard for ground water. The environmental risk of SPF is therefore very low, but because SPF is alkaline, its effect on soil pH should be taken into account. Implications : PMS is the solid waste resulting from the production of magnesium metal by Pidgeon's reduction process. Utilization of PMS in the high-technology and high-value areas may promote the high-efficiency development of worldwide collection metallic magnesium industry and contribute to the reduction of emissions of fine dust to air. This paper presents one of the new techniques in the use of PMS as a slow-release fertilizer by adding K2 CO3 . The product can serve as a very cost-effective and reliable artificial fertilizer.